Therapeutic Alliance in Cognitive Behavioural Therapy in Child and Adolescent Mental Health-Current Trends and Future Challenges - Fernandes, Hazel (Frontiers in Psychology, 2022)
This extended Literature review proposes to present the trends in Therapeutic Alliance , outcomes and measures in the last decade within the premises of Individual Cognitive Behaviour Therapy and its’ innovations, used as an interventional measure in the context of Child and Adolescent Mental Health Setting. A brief background of the rationale in conducting this literature search is presented at the start. This is followed by the Methodology and design which incorporates the inclusion and exclusion criteria and the basis for the same. The critical appraisal of the Primary studies is presented in the Literature review section with brief description of summary features of the studies in the Study Tables followed by Results and discussion of the study findings. To summarise, the literature review of Primary studies conducted in the last decade ,demonstrate the need for further research to be conducted ,both in the field of CBT in children as well as Therapeutic alliance, competence and therapy outcomes, integrating perspectives in child development, carer alliance and the social construct theory in children, to allow for further innovations in Cognitive Behaviour Therapy in the context of increasing challenges in the current times of exponentially developing technology and its’ utility without compromising quality of therapy. In conclusion, recommendations are made as a guideline for future studies and research in this field.